Pengaruh Likuiditas, Aktivitas, dan Penilaian Pasar Terhadap Harga Saham - Farisqie Yudha Pramukti; Yulita Setiawanta (Jurnal Akuntansi dan Pajak, 2022)
This research was purpose to analyze the effect of liquidity, activity, and market valuation on stock price from 11 samples of the Food and Baverages sub-sector companies listed on the IDX in the period 2016-2019. The types of financial ratios analyzed are Total Assets Turn Over, Earning per Share, and Current Ratio as independent variable and stock price as dependent variable. Purposive sampling method as sampling methodology and multiple linear regression method is used as statistical method in this research. From the results it can be shown that Earning per Share, Total Assets Turn Over, and Current Ratio in a simultaneous way have a significant effect to predict the stock prices. Partially the Total Assets Turn Over variable has a significant negative effect on predicting stock prices, and Earning per Share has a significant positive effect on predicting stock prices. Meanwhile Current Ratio has a negative and insignificant effect on predicting stock prices